Propping by controlling shareholders, wealth transfer and firm performance: Evidence from Chinese listed companies - Qianwei Ying; Liang Wang (China Journal of Accounting Research, 2013)
Propping acts by controlling shareholders are common in Chinese listed firms. In this paper, we use data on related-party transactions of all listed Chinese firms from 2002 to 2008 to investigate the motivation behind controlling shareholders' propping acts and subsequent wealth-transfer behavior and how both affect firm performance. We find that such institutional motivators as the maintenance of shell resources and qualification for refinancing have a significant effect on the propping behavior of controlling shareholders of Chinese listed firms and that such behavior is often followed by more serious tunneling when shareholders are driven by these motivators. Compared with non-state-owned firms, state-owned firms with the motivation to qualify for refinancing exhibit more severe tunneling after engaging in propping behavior. We also find that while propping by controlling shareholders improves a firm's current operating performance, in firms whose controlling shareholders' are motivated by the desire to maintain shell resources or obtain a refinancing qualification their performance declines in the following year because of subsequent tunneling. The results presented in this paper provide us with a better understanding of the relationship between propping and tunneling, controlling shareholders' engagement in both and the consequences of that behavior.
Keywords: 650; Propping; Wealth transfer; Tunneling; Firm performance